2011
DOI: 10.3945/ajcn.110.000802
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained chronic cough and vitamin B-12 deficiency

Abstract: This study suggests that Cbl-D may contribute to chronic cough by favoring sensory neuropathy as indicated by laryngeal hyperresponsiveness and increased NGF expression in pharyngeal biopsies of Cbl-D patients. Cbl-D should be considered among factors that sustain chronic cough, particularly when cough triggers cannot be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…On the contrary, Cbl up-regulates: (i) EGF levels in rat SC (by increasing its synthesis in neurons and glia) and CSF, and in human serum and CSF; and (ii) interleukin (IL)-6 levels in rat CSF Scalabrino, 2009). Most of the above findings have been confirmed by others (Battaglia-Hsu et al, 2009;Bucca et al, 2011;Ç eneli et al, 2010;Sampaio et al, 2013). The specificity of the cytokine and/or growth factor abnormalities induced by Cbl deficiency is demonstrated by their normalization after the Cbl replacement therapy in rats and patients with pernicious anemia, and the fact that the CSF levels of some neuropeptides and neurohormones Cbl as a fulcrum between physiologically myelinotrophic (green) and potential myelinodamaging agents (red) in rat CNS.…”
Section: Regulation Of the Cns Cytokine And Growth Factor Networksupporting
confidence: 62%
“…On the contrary, Cbl up-regulates: (i) EGF levels in rat SC (by increasing its synthesis in neurons and glia) and CSF, and in human serum and CSF; and (ii) interleukin (IL)-6 levels in rat CSF Scalabrino, 2009). Most of the above findings have been confirmed by others (Battaglia-Hsu et al, 2009;Bucca et al, 2011;Ç eneli et al, 2010;Sampaio et al, 2013). The specificity of the cytokine and/or growth factor abnormalities induced by Cbl deficiency is demonstrated by their normalization after the Cbl replacement therapy in rats and patients with pernicious anemia, and the fact that the CSF levels of some neuropeptides and neurohormones Cbl as a fulcrum between physiologically myelinotrophic (green) and potential myelinodamaging agents (red) in rat CNS.…”
Section: Regulation Of the Cns Cytokine And Growth Factor Networksupporting
confidence: 62%
“…Moreover, iron is required for proper myelination of the spinal cord (36). We recently found that deficiency of vitamin B‐12, a nutrient involved in myelin synthesis, may cause cough and laryngeal hyperresponsiveness through sensory neuropathy (37).…”
Section: Discussionmentioning
confidence: 99%
“…Cough-variant asthma (CVA) or nonasthmatic eosinophilic bronchitis (EB) (8) are other possible etiologies; iron and vitamin B-12 deficiencies are rare causes of CC (9,10).…”
Section: Introductionmentioning
confidence: 99%